2009
DOI: 10.3390/molecules14104098
|View full text |Cite
|
Sign up to set email alerts
|

Addition and Cycloaddition Reactions of Phosphinyl- and Phosphonyl-2H-Azirines, Nitrosoalkenes and Azoalkenes

Abstract: An overview of the use of 2H-azirines, conjugated nitrosoalkenes and conjugated azoalkenes bearing phosphorus substituents in addition and cycloaddition reactions is presented, focused on strategies for the synthesis of aminophosphonate and aminophosphine oxide derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…After brief optimization of the reaction conditions (solvent, base and ratio of reagents), it was found that alkylation of benzylamine with 2.0 equiv of Boc-hydrazone 1a and 2.0 equiv of potassium carbonate as a base in MeOH led to bishydrazone 2a in highest yield. The bright yellow color appeared in course of reagents mixing indicating the formation of azoalkene intermediate A [3539]. Under these conditions, a range of other α-halogen hydrazones 1b–d , f , g were successfully converted to corresponding bishydrazones 2b–d , f , g in good to high yields (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After brief optimization of the reaction conditions (solvent, base and ratio of reagents), it was found that alkylation of benzylamine with 2.0 equiv of Boc-hydrazone 1a and 2.0 equiv of potassium carbonate as a base in MeOH led to bishydrazone 2a in highest yield. The bright yellow color appeared in course of reagents mixing indicating the formation of azoalkene intermediate A [3539]. Under these conditions, a range of other α-halogen hydrazones 1b–d , f , g were successfully converted to corresponding bishydrazones 2b–d , f , g in good to high yields (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, we focused on the development of a general approach to tertiary amines and polyamines bearing several hydrazonomethyl arms at the nitrogen atom(s). To achieve this goal, we suggested a straightforward methodology based on multiple Michael-type additions of azoalkenes A (generated from α-halogen azacarbonyl precursor 1 [3539]) to amines or ammonia (Scheme 1). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Azoalkenes (1,2-diaza-1,3-dienes) 4 ( Scheme 2 ) are structurally and electronically related to 1-oxa-2-aza-1,3-dienes 2 ( Scheme 2 ) and currently attract great attention as versatile substrates for hetero -Diels-Alder reactions performed with various dienophiles. The importance of this research is reflected by a large number of excellent review articles, which appeared in the last two decades [ 23 , 24 , 25 , 26 , 27 ]. Numerous original publications appear regularly.…”
Section: Introductionmentioning
confidence: 99%
“…The past several decades confirmed conjugated azoalkenes (also called 1,2-diaza-1,3-dienes or DDs; e.g., Scheme , heterodienes 2 or 5 ), mostly obtained via dehydrohalogenation of the respective α-halo-hydrazones 1 or 4 (Scheme ), as powerful intermediates in the synthesis of an impressive number of new heterocyclic systems either through hetero Diels–Alder cycloaddition or 1,4-conjugate addition reactions. Examples of these reactions are shown in Scheme . , …”
mentioning
confidence: 99%